Carbon-substrate utilization profiles by Cladorrhinum (Ascomycota) - Barrera, Viviana Andrea (2019)
Fungi from the genus Cladorrhinum (Ascomycota) are promising agents in the biocontrol of phytopathogens, in the promotion of plant growth, and in the production of enzymes with technological application. We analyzed comparatively the ability of 5 native strains of Cladorrhinum samala and Cladorrhinum bulbillosum with reference strains belonging to the same genus. We used 95 individual carbon sources available in microplates from the Biolog® FF system. Although most of the strains mainly used soluble carbohydrates, the metabolic profile was highly dependent upon each isolate and it revealed intraspecific physiological variability in Cladorrhinum species.